(untitled) (CIPEEX, 2024)
THE AIM OF THIS WORK IS TO ANALYZE THE UTOPIA OF REHABILITATING OFFENDERS IN CASES OF SEXUAL CRIMES COMMITTED AGAINST CHILDREN AND ADOLESCENTS AND, THUS, OBSERVE THAT THE PENALTIES IMPOSED IN THESE CRIMES ARE NOT SUFFICIENT FOR THE OFFENDER TO BE PROPERLY REHABILITATED, SINCE THIS FACT IS PROVEN BY THE RECURRENCE OF THESE CRIMES. THE STUDY SOUGHT TO UNDERSTAND THE FACTORS INFLUENCING THE REINTEGRATION OF THESE OFFENDERS INTO SOCIETY, THE PERSPECTIVES OF THE VICTIMS AND PROFESSIONALS INVOLVED, AS WELL AS THE CHALLENGES AND ETHICAL IMPLICATIONS ASSOCIATED WITH THIS PROCESS. THE VICTIMS’ PERSPECTIVES EMPHASIZE THE NEED TO BALANCE REHABILITATION WITH PROTECTIVE MEASURES. MANY OFFENDERS CONTINUE TO COMMIT SEXUAL CRIMES, INDICATING THE NEED FOR MULTIDISCIPLINARY AND INDIVIDUALIZED APPROACHES. THE RESEARCH WAS CONDUCTED THROUGH A LITERATURE REVIEW, HIGHLIGHTING THE COMPLEXITY OF REHABILITATION IN THIS CONTEXT AND UNDERSCORING THE IMPORTANCE OF THE QUALITY OF REHABILITATION PROGRAMS, FAMILY SUPPORT, AND MENTAL HEALTH SERVICES. HOWEVER, THE RESULT OBTAINED IS THAT REHABILITATING OFFENDERS IN SEXUAL CRIMES AGAINST CHILDREN AND ADOLESCENTS IS A MULTIFACETED CHALLENGE. RECIDIVISM IS A CONCERNING REALITY, REQUIRING MORE INCISIVE AND TAILORED APPROACHES, SUCH AS THE POSSIBILITY OF IMPOSING HIGHER AND DISTINCT PENALTIES FROM THOSE ALREADY ESTABLISHED FOR THE BEGINNING OF THE SENTENCE, AS THESE HAVE PROVEN INEFFECTIVE, WHILE ALWAYS RESPECTING THE RIGHTS PROVIDED IN THE LEGAL SYSTEM. FURTHERMORE, VICTIM PROTECTION SHOULD BE PRIORITIZED, AS WELL AS OVERCOMING THE STIGMA. A MULTIDISCIPLINARY AND INNOVATIVE APPROACH IS ESSENTIAL, INVOLVING VARIOUS PROFESSIONALS. THIS REVIEW HIGHLIGHTS THE NEED FOR A CONTINUOUS COMMITMENT TO VICTIM PROTECTION AND HOLDING OFFENDERS ACCOUNTABLE, RESPECTING THE RIGHTS AND DIGNITY OF ALL PARTIES INVOLVED.